2018
DOI: 10.7567/jjap.57.081302
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kinetic of hydrogen in CH3O-molecular-ion-implanted silicon wafer for CMOS image sensors

Abstract: The association and dissociation behavior of hydrogen in the implanted region of a CH 3 O cluster were investigated for high-performance CMOS image sensors. Two hydrogen peaks were observed in the CH 3 O-implanted region after epitaxial growth and heat treatment. The difference in the depths of the two peaks accords with the difference in the depth of carbon-cluster-related and new extended stacking fault defects. Thus, we calculated the activation energies of the association and dissociation of hydrogen, assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Third, we demonstrated that the hydrogen out-diffused to silicon epitaxial layer (device active region) from hydrogen storage in hydrocarbon–molecular–ion projection range during the heat treatment [35,65,66]. This hydrogen of out diffusion amount is 10 12 to 10 13 cm −2 measured by SIMS after heat treatment [70]. It is well known that Si/SiO 2 interface state density in MOS transistor device is approximately 10 10 to 10 11 cm −2 [71].…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
“…Third, we demonstrated that the hydrogen out-diffused to silicon epitaxial layer (device active region) from hydrogen storage in hydrocarbon–molecular–ion projection range during the heat treatment [35,65,66]. This hydrogen of out diffusion amount is 10 12 to 10 13 cm −2 measured by SIMS after heat treatment [70]. It is well known that Si/SiO 2 interface state density in MOS transistor device is approximately 10 10 to 10 11 cm −2 [71].…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
“…Therefore, the shallower peaks in the H, C, and N profiles correspond to C/I clusters, and the deeper peaks correspond to stacking faults. Okuyama and coworkers reported that H at high concentrations can be trapped in C 3 H 5 and CH 3 O ion‐implanted regions by C/I clusters and/or stacking faults immediately after the epitaxial growth of the Si layer . Therefore, the existence of high concentrations of H atoms in the CH 4 N ion‐implanted region may also be responsible for the C/I clusters and stacking faults.…”
Section: Resultsmentioning
confidence: 99%
“…Okuyama and coworkers reported that H at high concentrations can be trapped in C 3 H 5 and CH 3 O ion-implanted regions by C/I clusters and/or stacking faults immediately after the epitaxial growth of the Si layer. [14,34] Therefore, the existence of high concentrations of H atoms in the CH 4 N ion-implanted region may also be responsible for the C/I clusters and stacking faults. In addition, there is a possibility that N atoms also segregate around the C/I clusters and stacking faults with H and C atoms.…”
Section: Trapping Behavior Of Implanted Atoms In Ch 4 N Ion-implanted...mentioning
confidence: 99%
“…[37][38][39] 30 We used L 2 = 1.3 × 10 −12 exp (−0.75/kT) cm 3 /s reported in a previous study. 30 We tried to derive L 1 by fitting with the experimental results of D it heat-treatment time dependence. Figure 6 shows the result of fitting the D it plots using Eq.…”
Section: Simentioning
confidence: 99%
“…29 It has also been reported that the hydrogen concentration in the CH 3 O-molecular-ion implanted region increases owing to the endof-range (EOR) defects. 30 Therefore, CH 3 O-implanted wafers are expected to have a better hydrogen termination effect than hydrocarbon-molecular-ion-implanted wafers. It is essential to reduce D it at the SiO 2 /Si interface to reduce the noise in high-performance CMOS image sensors in the future.…”
mentioning
confidence: 99%